2018
DOI: 10.1186/s12935-018-0623-y
|View full text |Cite
|
Sign up to set email alerts
|

ZFAS1: a novel tumor-related long non-coding RNA

Abstract: Long non-coding RNAs (lncRNA) are classified as a kind of RNA, which are longer than 200 nucleotides in length and cannot be translated into proteins. Multiple studies have demonstrated that lncRNAs are involved in various cellular processes, including proliferation, differentiation, cell death, and metastasis. In addition, aberrant expression of lncRNAs has been discovered in human tumors, where they function as either oncogenes or tumor suppressor genes. Among numerous lncRNAs, we focus on ZNFX1 antisense RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 57 publications
0
65
0
Order By: Relevance
“…[7][8][9] Zinc finger antisense 1 (ZFAS1), a member of lncRNAs, has been demonstrated to be a novel vital oncogenic ln-cRNA. 10,11 ZFAS1 is implicated in the occurrence and development of various cancers, including gastric cancer, ovarian cancer and hepatocellular carcinoma. 10 However, the role of ZFAS1 in glioma has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Zinc finger antisense 1 (ZFAS1), a member of lncRNAs, has been demonstrated to be a novel vital oncogenic ln-cRNA. 10,11 ZFAS1 is implicated in the occurrence and development of various cancers, including gastric cancer, ovarian cancer and hepatocellular carcinoma. 10 However, the role of ZFAS1 in glioma has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…6,13 Latest evidence on tumorigenesis has revealed that lncRNAs play a vital role in the tumorigenesis of many forms of cancers, 6,13 and several oncogenic lncRNAs, such as NEAT1, 7,14 MALAT1 15,16 and PVT1, 17 are well established. In addition, certain other lncRNAs, such as GAS5 18 and ZFAS1, 19 have been shown to act as tumour suppressors during carcinogenesis.…”
mentioning
confidence: 99%
“…There are variable results with the examination of ZFAS1 in the literature. 111 ZFAS1 has previously been shown to have a tumor suppressive function in breast cancer by decreasing both cell proliferation and migration. 141,142 Examination of ZFAS1 in hepatocellular carcinoma has shown that it can have both a tumor suppressive and oncogenic function through different mechanisms.…”
Section: Chapter XI Discussion and Concluding Remarksmentioning
confidence: 99%
“…There is therefore, a need to characterize the lncRNA expression profile for a specific cancer subtype. 111 Some investigators have shown that lncRNAs can have paradoxical effects in different cancers, which further underscores the reason for investigation in a particular cancer subtype. 111 The identification of differentially expressed lncRNA between colon adenocarcinoma and normal colon epithelium is important, as this may demonstrate lncRNAs that may be important in colon cancer carcinogenesis.…”
Section: Other Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation